1994
DOI: 10.1038/bjc.1994.225
|View full text |Cite
|
Sign up to set email alerts
|

p53 mutations and overexpression in locally advanced breast cancers

Abstract: Summary Alterations in the p53 gene were analysed in 39 patients with locally advanced breast cancers (LABCs) (stage III-IV) with inflammatory signs in most cases (UICC stage T4d = 32 patients) by molecular and immunohistochemical (IHC) approaches. All patients were included in the same therapy protocol. Using polymerase chain reaction (PCR) and a single-strand conformational polymorphism migration technique (SSCP), the presence of mutations in exons 2-11, covering the entire coding sequence of the p53 gene, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1

Year Published

1996
1996
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 40 publications
2
24
1
Order By: Relevance
“…The Ala125Val mutant p53 gene was isolated from the carcinoma indicating that the more aggressive mammary tumour of patient 5 was associated with a point mutation of the canine p53 gene. Such an association between p53 mutation and high grade tumours has been noted previously in human breast cancer patients (Faille et al, 1994;Berns et al, 1996;Hartmann et al, 1997). The observed C to T transition mutation of patient 5 may have been the result of de-amination of 5-methylcytosine at the CpG position within codon 125 (GCG).…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…The Ala125Val mutant p53 gene was isolated from the carcinoma indicating that the more aggressive mammary tumour of patient 5 was associated with a point mutation of the canine p53 gene. Such an association between p53 mutation and high grade tumours has been noted previously in human breast cancer patients (Faille et al, 1994;Berns et al, 1996;Hartmann et al, 1997). The observed C to T transition mutation of patient 5 may have been the result of de-amination of 5-methylcytosine at the CpG position within codon 125 (GCG).…”
Section: Discussionsupporting
confidence: 61%
“…This is consistent with a number of human p53 mutants that contain amino acid substitutions within the highly conserved central core domain (for example, see Rolley et al, 1995). Adoption of the mutant conformation is suggested to contribute to nuclear accumulation of mutant p53 protein within tumour cells (Faille et al, 1994). Indeed, the corresponding human p53 mutant, Ala138Val, has been shown to display an increase in nuclear p53 protein levels within breast cancer cells (Moll et al, 1992;Faille et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to previous findings (Kern et al, 1989), when tumours were classified according to their histological stage, a multivariate Cox model analysis showed that p53 mutation, rather than 17p allelic losses, was the only independent prognostic factor (Hamelin et al, 1994). Immunohistochemistry (IHC) studies have indicated that mutated p53 is overexpressed in premalignant head and neck lesions (Shin et al, 1994), oesophageal squamous cell carcinomas (Wagata et al, 1993), ovarian cancer (Kupryjanczyk et al, 1993), breast cancer (Faille et al, 1994) and hepatocellular carcinoma (Wolkmann et al, 1994). In colorectal cancer, overexpression of p53 protein has been correlated with poor short-term prognosis (Yamaguchi et al, 1992; p53 mRNA overexpression in colorectal cancer 529 1 00C 1OC 10 100'…”
mentioning
confidence: 95%